Discussion on transient electromagnetic detection transmitting frequency of groundwater in fire-burned rock in Jundong coalfield - Qiang WANG; Fei LING; Siwei LI; Liqiang FAN; Yuan LIU; Peng WANG; Bo HE; Chao WANG; Xi ZHENG; YILIHAMUJIANG·Tuniyazi; Xudong FAN (Meikuang Anquan)
In order to determine the optimal transmitting frequency when we use transient electromagnetic method to detect groundwater in fire-burned rock in Jundong Coalfield, theoretical analysis, forward and inverse calculation and field test are used to conduct comparative analysis on the effects of rising edge time, formation resistivity and transmitting frequency, respectively. The results show that: the strata in Jundong Coal Field have low resistivity (about 10-40 Ω·m), and the groundwater in fire-burned rock has ultra-low resistivity (about 4.0 Ω·m). When the transmitting frequency is too high, it is easy to affect the transient electromagnetic secondary field signal because the field construction time is too short. In particular, the induced signal strength weakens with the increase of the rising edge time, and this effect is more obvious when the formation resistivity decreases. The forward and inversion results show that both 25.0 Hz and 8.3 Hz transmitting frequencies can reflect the induced signal of groundwater in fire-burned rock, but the 25.0 Hz result is weaker than that of 8.3 Hz. The field test found that at the shutdown time of 25.0 Hz transmitting frequency, the ground still had residual induction field, which did not meet the requirements of transient electromagnetic technology. The geoelectric section corresponding to the inversion was inconsistent with the actual situation and did not reflect the rich water area in fire-burned rock. However, there was no such problem at 8.3 Hz transmitting frequency. It is concluded that the transient electromagnetic method cannot obtain accurate detection results when the transmitting frequency is too high in Jundong Coal Field. When the transmitting frequency of 8.3 Hz is matched with the combined parameters of 400 m×400 m emission loop and 11 A emission current, the distribution of fired rock water can be accurately reflected. The combined parameters can be used for reference and promotion in mining areas with similar geological conditions. The factors that determine the optimal transmitting frequency are the time of field construction, the depth of detection and the working efficiency, and the transmitting frequency should be selected as high as possible on the basis of sufficient time of field construction and observation.